Trends Research and Publication of Master Students in Science Education Program - Eko Hariyono; Titin Sunarti; Fenny Roshayanti; Hasan Nuurul Hidaayatullaah; Desi Wulandari (IKIP Mataram, 2022)
College students' creativity can be seen based on the novelty of research. The main objective of this study was to analyze trends research and publicationof the master of science education at the State University of Surabaya. The descriptive qualitative method used in this study. The data of this study collected by analyse the last five years research abstracts from 2015 to 2020. The data obtained were analyzed using a total sampling technique. Research trends and publication in the Master of Science education at the State University of Surabaya are mostly researching about the development of learning tools with qualitative-quantitative methods and research topics about innovative learning in the field of thinking skills. Some college student research uses curriculum topics, learning media, and assessments. While the publication trend is obtained by analyzing the publication of student articles resulting from the thesis based on the analysis of publications in the category of international and national journals. Department heads need policy recommendations in making decisions to improve research trends and college student publications. current study result implies that research trends in the Master of Science education at the State University of Surabaya require further innovation.